PENGAMANANOBJEK VITAL NASIONAL OLEH DIREKTORAT PENGAMANAN OBJEK VITAL POLDA KALIMANTAN SELATAN - Army Fuad Helmy (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
This research aims to: (1) Assess and evaluate the pattern containedsystem in the Securing of National Vital Objectsby Vital Object Security Directorate of Polda Kalimantan Selatan; and (2) Assess and evaluate the obstacles in the Securing of National Vital Objects by Vital Object Security Directorate of Polda Kalimantan Selatan. It can be concluded that: 1. The system pattern contained in the Securing of National Vital Objects by Vital Object Security Directorate of Polda Kalimantan Selatan not stated clearly and explicitly in the legislation pam obvitnas, but in the Presidential Decree No. 63 of 2004 on the Securing of National Vital Security Object there is described that pattern Sispamobvitnas, they are: (1) The main executor of the system Securing of National Vital Objek is obvitnas management authority, in this case the Police through Dirpamobvit; (2) Police are obliged to provide security assistance obvitnas; (3) priority preemptive and preventive activities; (4) in an integrated and simultaneous shared obvitnas managers implement security systems obvitnas; and (5) and against obvitnas is an organic part of or including the military, the security environment remain to be implemented, although the security environment outside Obvitnas or process interruption handling defense and security. 2. The obstacles in the Securing of National Vital Objects by Vital Object Security Directorate of Polda Kalimantan Selatan, they are: (1) Lack of quality personnel guard PT. Pertamina (Persero) BBM Terminal Banjarmasin due to lack of professional recruitment system; (2) Insufficient number of security officers compared to the vulnerability of the region; (3) Infrastructure security Obvit Of Polda Kalimantan Selatan are limited;(4) The lack of security coordination between Ditpamobvit Polda Kalimantan Selatan with regional security managers of the company, and the company's internal security guard at the Police Post.